Internet economics guide - St. Hill, R. L. (Prentice Hall/Pearson Education Australia, 2001)
Designed to help students of economics explore the Internet and discover useful paths to understanding the ever changing field of economic theory and practice. Using the Internet, it teaches students how to identify information requirements, find the information and turn it into knowledge.